Counseling on Productive Economic Business Empowerment for the Communities of Muara Kumbang Village, Kandis Sub-District, Ogan Ilir District - Pratama, Akram; Fitria, Dinda; Ilham, M.; Puput, Puput; Zubaidah, Zubaidah; Delimawati, Delimawati; Fatri, Tri; D., Sukaria (Altifani Journal: International Journal of Community Engagement, 2021)
Empowerment is an effort to create changes in the human environment by using one's own efforts and abilities to meet the needs of life independently. Based on the situation analysis conducted in Muara Kumbang village, Kandis sub-district, Ogan Ilir district, it is very necessary to do community service with the theme of "Empowering Productive Economic Enterprises" (UEP) to improve the community's economic business. The PKM program was held on Tuesday, September 14, 2021 in Muara Kumbang village, Kandis District, Ogan Ilir Regency, South Sumatra. There were 25 participants in the training program. The method used consists of interviews and observations of participants regarding their understanding of the empowerment of productive economic enterprises. The results of the interview revealed that only about 40% of the participants understood it. In the final interview and observation, it showed changes and improvements, namely the increasing number of participants who understood the empowerment of productive economic enterprises, from only 40% to 80%.